(untitled) (Inflexion Point Magazine, 2026)
Among the techniques that allow us to know the function of the brain, practically in real time, are electroencephalography and Functional Near Infrared Spectroscopy (fNIRS). In addition, they are considered minimally invasive techniques, as they require at least contact with the skin of the person to be evaluated. a Electroencephalography measures the electrical activity of neurons, using methods that record the activity, such as synapses. (fNIRS) measures changes in oxygen concentration providing information on cognitive, emotional and neurological processes, useful in research and clinical diagnosis, allowing a glimpse into the brain.